2020
DOI: 10.21203/rs.3.rs-95527/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Individuals With Eating Disorders: the Role of Emotion Regulation and Exploration of Online Treatment Experiences

Abstract: Objective: The Covid-19 pandemic has wrought disruption to everyday life and services, and emerging evidence suggests that those with eating disorders (EDs) are likely to experience marked distress and exacerbation of their symptoms. However, little is known around the most relevant factors to symptom change; whether certain emotion regulation and coping strategies are linked to better outcomes; and how people with EDs are adjusting to psychological interventions moving online. Method: In a mixed-method design… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
(133 reference statements)
0
9
0
Order By: Relevance
“…Future studies should clarify the reasons that determine whether the pandemic is more of an opportunity or a challenge for eating disorder patients. First studies indicate that differences in emotion regulation and coping skills as well as personality factors may play a crucial mediating role [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should clarify the reasons that determine whether the pandemic is more of an opportunity or a challenge for eating disorder patients. First studies indicate that differences in emotion regulation and coping skills as well as personality factors may play a crucial mediating role [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the outbreak of the covid-19 crisis and the resulting lockdown, the need emerged to find solutions for the continuation of treatment in adolescents and young women with EDs (45)(46)(47). This need led to the adaptation of ED-related treatment to a long-distance online home-based telemedicine format (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Current studies indicate an exacerbation of both behavioral and emotional ED-related symptoms with the advent of the COVID-19 pandemic and subsequent lockdowns (46,48). Patients face in these conditions difficulties related to greater involvement of their families with their eating, and having more unplanned free time, alongside changes in their sleeping routine and screen time, and decreasing outside physical activity (46,49).…”
Section: Eds During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Although knowledge about the symptoms of eating disorders and negative body image during the COVID-19 pandemic has increased in diverse populations [ 13 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], research and knowledge on the symptoms of eating disorders and body image in Polish women remains limited (Polish studies published so far have concerned either the period before the pandemic [ 31 ] or a general problem of nutrition behaviors before and during COVID-19 lockdown [ 32 ]). Given the likelihood that the pandemic, attendant restrictions, and their consequences have been a source of chronic and severe stress and anxiety [ 4 , 5 , 6 , 7 , 8 , 9 ], and, as earlier research indicated, may have had an impact on body image and eating disorder symptomatology [ 10 , 13 , 14 ], it is vital to develop a fuller understanding of this issue in Polish women.…”
Section: Introductionmentioning
confidence: 99%